The Influence of Profitability, Liquidity, Company Size, Asset Growth, Asset Structure, and Business Risk on the Capital Structure of Technology Sector Companies - Paranita, Ekayana Sangkasari; Rezina, Aulia Melinda (Journal of Applied Management Research, 2025)
This study aims to determine the effect of profitability, liquidity, company size, asset growth, asset structure, and business risk on capital structure. The control variables in this study are firm size and leverage. This type of research uses a quantitative approach. The population in this study comprises technology sector companies listed on the IDX for the 2020–2022 period, totaling 34 companies. The sampling technique employed in this study utilized a purposive sampling method, involving a sample of 14 technology sector companies and a total of 42 pieces of data. The data were analyzed using multiple linear regression. The data collection used in this study is secondary, derived from financial reports on the Indonesian Stock Exchange. The results of this study indicate that 1) Profitability does not affect capital structure. 2) Liquidity has a positive and significant effect on capital structure. 3) Company size does not affect capital structure. 4) Asset growth does not affect capital structure. 5) The asset structure does not affect the capital structure. 6) Business risk does not affect capital structure. 7) Profitability, liquidity, company size, asset growth, asset structure, and business risk all have a significant effect on capital structure simultaneously. 8) Firm age as a control variable does not affect capital structure. 9) Leverage as a control variable has a positive and significant effect on capital structure.